HCl-mediated phase reconstruction: A facile approach for selective Ca and Mn recovery from stainless steel slag - Zhen Wu; Qiuyun Huang; Qian Wang; Junwu Song; Hongbo Du; Han Song; Fenghua Ding; Zhang Lin (Journal of Environmental Chemical Engineering, 2026)

Microbial diversity and technological characterization of lactic acid bacteria in traditional fermented yak dairy products from Huangnan Prefecture, Qinghai, China - Hongbo Li; Geng Long; Jiali Zhu; Lin Yang; Hongjuan Li; Jinghua Yu (International Dairy Journal, 2026)

Circulating polymer-resolved microplastics in pediatric epilepsy: higher internal burden in drug-resistant cases - Ziyu Liu; Yulei Sun; Neng Ren; Hongbo Zhang; Yuhan Lin; Lingyun Wang; Guoliang Li; Ying Zhang; Bo Zhang (Environmental Pollution, 2026)

Hierarchical interfacial electric field engineering: Integrating plasmonic oscillation and dipole broadening for efficient perovskite solar cells - Hui Duan; Lexin Wang; Xiaoye Liu; Xinxuan Yang; Fengyou Wang; Hongbo Liu; Lin Fan; Jinghai Yang; Lili Yang (Chemical Engineering Journal, 2026)

Driven magnetic 3D DNA walker coupled with CHA based on light-activatable hairpin: A dual-amplification strategy for ultrasensitive hantavirus RNA sensing - Haimei Lin; Ziyi Wang; Shiwen Liu; Suqin Wang; Hongbo Li; Ruqin Yu (Analytica Chimica Acta, 2026)

Spatial patterns and ecological transition potential of high-abandonment-risk cropland in China: A MaxEnt-based assessment - Dan Lu; Zhanpeng Wang; Yuqing Zhu; Hongbo Zhao; Jingjing Liu; Haipeng Zhang; Aiwen Lin (Environmental Impact Assessment Review, 2026)

See and destroy bacterial spores: Visual detection and in situ inactivation using a terbium-porphyrin nanoplatform - Shan Sun; Ke Cheng; Jiayi Feng; Hongbo Juan; Kefeng Zhou; Mingyan Zhao; Heng Zhang; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

Correction: Phylogenetic analysis, genetic diversity, and epidemiology of pigeon paramyxovirus type 1 in China - Chuqi Huang; Shaoyu Tu; Wei Sheng; Zhihao Wang; Zhipeng Lin; Jing Qian; Jiahui Zou; Hongbo Zhou (Archives of Virology, 2026)

SIFFNet: A semantic information feature fusion network for suppressing diverse DAS-VSP noise - Hongbo Lin; Shishuai Li; Qingchen Yang; Zeyuan Zhang; Junhan Chen (Computers & Geosciences, 2026)

Computation-driven discovery of a next-generation canine monoclonal antibody for canine parvovirus therapy - Ying Li; Xiaoyu Zhang; Zhihao Wang; Mingqin Lin; Sheng Wang; Chengguang Zhang; Ling Zhao; Jiahui Zou; Hongbo Zhou (Veterinary Microbiology, 2026)

RCTUnet: a deep learning model for crop-residue-soil image segmentation and crop residue cover extraction - Ting Li; Yang Liu; Haikuan Feng; Meiyan Shu; Hao Yang; Yuanyuan Fu; Xin Xu; Yinghao Lin; Hongbo Qiao; Wei Guo; Xinming Ma; Lei Shi; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Analysis of Physical Driving Factors for Long-Term Evolution of Chlorophyll a Concentration in the South China Sea - Caiqin He; Guodong Ye; Chunqiao Lin; Xirui Xu; Hongbo Deng; Weiying Gong; Jianjun Xu; Lingli Fan (Journal of Marine Science and Engineering, 2026)
In the context of global warming, the South China Sea is showing an accelerating warming trend, which highlights the impact of climate change on the marine environment of the South China Sea. The interdecadal variation of chlorophyll a concentration (Chl_a) directly reflects the long-term evolution pattern of the upper marine ecological environment in the South China Sea and has significant indicative significance for marine ecological protection. This study investigated the relationships between Chl_a concentration, sea surface temperature (SST), shortwave radiation (SSRD), mixed layer depth (MLD), wind speed (Wind), and geostrophic current (ugo) in the South China Sea over the past 27 years. Statistical methods were used to analyze the differentiated impacts of marine environmental factors under different climate backgrounds on Chl_a concentration. From 1998 to 2007 (P1), there was a decreasing trend in the early stage, from 2007 to 2015 (P2), there was an upward trend in the middle period, and from 2015 to 2024 (P3), there was an upward trend in the recent period. During these three stages, SST and MLD were the core influencing factors. The threshold of SST gradually increased over time, reaching 27.05 °C, 27.24 °C, and 27.32 °C, respectively. The average normalized information flow (NIF) of Chl_a concentration changed from positive to negative. In the early stage of P1, the SST in most areas of the South China Sea was less than 27.05 °C, and in the P2 and P3 periods, the SST in most areas reached the threshold. The thresholds of MLD were 22.33 m, 21.64 m, and 33.68 m, respectively. The average NIF of Chl_a concentration was positive in all periods. The MLD in most areas of the South China Sea did not reach the threshold in all three periods. These findings emphasize the different roles of marine environmental factors in regulating Chl_a concentration in the South China Sea, providing a scientific basis for the ecological health monitoring of marine fishery areas, disaster warning, and adaptive management in response to climate warming.

Transcriptomic analysis identifies VvMYB90 and VvNAC92 as key regulators mediating anthocyanin biosynthesis and fruit color differentiation in three grape cultivars - Han Lin; Kaili Mao; Shilong Chai; Jiangmin Lan; Hongbo Xiao; Zhixiong Guo; Tengfei Pan; Wenqin She (Plant Science, 2026)

Concomitant exposure to residential greenness, nitrogen dioxide, and outdoor light at night in association with incident anxiety - Jiayun Zhang; Yexiang Sun; Zihan Li; Lisha Xu; Jingjing Hu; Jie Qiu; Xinhan Zhang; Zongming Yang; Zhanghang Zhu; Yonghao Wu; Yixing Wang; Hongbo Lin; et al. (Landscape and Urban Planning, 2026)

New Gyrodactylus Species (Monopisthocotyla: Gyrodactylidae) on Freshwater Goby Rhinogobius giurinus (Perciformes: Gobiidae) in China - Hongbo Nie; Zhiyu Lin; Zhizhen Liu; Jia Cai; Kwaku Amoah; Xiao Jin; Jichang Jian (Acta Parasitologica, 2026)

Impact of embedded tunnels on seismic response of saturated sandy ground: Insights from 1 g shaking table tests and CFD-DEM simulations - Mingze Xu; Zixin Zhang; Xin Huang; Hongbo Zhou; Nan Lin (Tunnelling and Underground Space Technology, 2026)

Molecular detection of rusts resistance loci and viruses specific sequences for screening sugarcane germplasm against mosaics, yellow leaf and rusts - ChunYan Kong; Jun Mao; ChaoHua Xu; Kamal Priyananda Wickramasinghe; ShengXian Chen; HongBo Liu; XiuQin Lin; XuJuan Li; ChunYan Tian; Xin Lu (Euphytica, 2026)

Associations of concomitant exposure to outdoor light at night, air pollution, and greenness with metabolic syndrome: A cohort study in China - Lisha Xu; Yexiang Sun; Zihan Li; Jiayun Zhang; Yichao Dai; Ye Jiao; Zhanghang Zhu; Jingjing Hu; Jie Qiu; Yixing Wang; Hongbo Lin; Liming Shui; et al. (Environmental Research, 2026)

Elimination performance of NOx and chlorobenzene over VOx/TiO2-based commercial SCR catalysts at low temperature: Sulfur poisoning and regeneration - Yunfeng Ma; Jiayao Wu; Jianwen Lai; Hongbo Qi; Fanxiang Meng; Bingcheng Lin; Rong Jin; Zhongkang Han; Minghui Zheng; Xiaodong Li; Xiaoqing Lin (Chemical Engineering Journal, 2026)

Synergistic coacervation–micelle extraction enables rapid and efficient removal of ultrahigh–concentration organic dyes from wastewater - Tao Wang; Qiongyao Peng; Yongxiang Sun; Pan Huang; Lin Yang; Hongtao Ma; Xuwen Peng; Haoyu Yang; Yimei Sun; Diling Yang; Ying Hu; Jifang Liu; et al. (Chemical Engineering Journal, 2026)

Experimental investigation and characterization of the vibration fatigue S-N curve for small-diameter 316L stainless steel butt-welded pipes - Ning Li; Hongbo Gao; Lei Lin; Pin Li; Shuai Zhou; Han Liu; Changning Li; Decheng Xu; Yin Liu; Zhilin Chen (Annals of Nuclear Energy, 2026)

Walkability, fine particulate matter and risk of Osteoporosis: A cohort study in China - Jie Qiu; Peng Shen; Jingjing Hu; Zhanghang Zhu; Lisha Xu; Jiayun Zhang; Zihan Li; Hongbo Lin; Liming Shui; Feng Tong; Kun Chen; Jianbing Wang (Atmospheric Environment, 2026)

Adverse drug-event detection using the tree-based scan statistics (TreeScan) and comparison with common mining methods: new user, propensity score-matched cohorts - Hailong Li; Houyu Zhao; Hongbo Lin; Peng Shen; Lingli Zhang; Siyan Zhan (European Journal of Clinical Pharmacology, 2026)

Predicting the performance of microbial electrochemical systems equipped with three-dimensional anodes using machine learning - Jiannan Li; Honglin Chen; Yijie Lin; Hongbo Mai; Yanfang Song; Ye Qiu; Guohong Liu; Yujie Feng (Journal of Environmental Chemical Engineering, 2025)

Comparative study of machine learning and deep learning in predicting the shear strength of marine sand and polymer layer interfaces interface under marine temperature effects - Zhiming Chao; Yanqi Liu; Dongbo Jiang; Hongbo Du; Wei You; Xianhui Feng; Jie Lin; Peng Cui; Zejin Wang (Frontiers in Marine Science, 2025)
In marine engineering, polymer layers are anti-seepage barrier materials. The mechanical interaction between marine sand and polymer layer significantly affects overall structural stability. In this study, direct shear tests at different temperatures in the marine environment are simulated to evaluate the shear behavior of marine sand and polymer layer interface, and a database is developed. Based on the experimental data, the study employs the Back propagation Neural Network (BPNN), Genetic Algorithm and Particle Swarm Optimization BPNN, and convolutional neural network (CNN) models, which are trained and tested. The findings show that the CNN algorithm significantly outperforms other models in terms of prediction accuracy and efficiency. Sensitivity analysis shows that temperature, shear displacement, normal stress, and particle size have influence on interfacial shear strength, and the impact of normal stress is the greatest. In addition, an empirical formulation is proposed to provide tools for those without machine learning. Based on the research results, the deep learning CNN model developed in the study can accurately predict the shear strength of the interface between marine sand and the polymer layer, which provides an effective tool for the design and optimization of marine engineering.

Protective Effects of Deinoxanthin on Brain Oxidative Damage and Gut Microbiota in the D-Galactose-Induced Aging Mice - Huijuan Su; Yutao Li; Jiayi Wan; Jieyu Lin; Jiayao Wang; Rui Fan; Dingming Liu; Jing Wei; Hongbo Xin; Yuejin Hua; Shengjie Li (Molecular Neurobiology, 2025)

Residential green space and transition trajectory of cardiometabolic multimorbidity in two prospective cohorts - Yonghao Wu; Jiacheng Ying; Yexiang Sun; Lisha Xu; Zihan Li; Jiayun Zhang; Jie Qiu; Yixing Wang; Jingjing Hu; Peng Shen; Hongbo Lin; Liming Shui; et al. (Urban Forestry & Urban Greening, 2025)

Exploring controls on precipitation-runoff dependencies: Implications for non-stationary and spatially heterogeneous analyses - Tian Lan; Xinyue Du; Xue Xie; Kairong Lin; Hongbo Zhang; Xinghui Gong; Yongqin David Chen; Chong-Yu Xu (Journal of Hydrology, 2025)

Light-driven CO2 reduction for acetate production by coupling photocatalyst CdS with acetogenic bacteria Clostridium aceticum: An insight into the electron transfer pathway - Bo Fu; Wei Lin; Hui Zhao; Shijian Yang; Jingyi Han; Qihao Cao; He Liu; Hongbo Liu; Jieshu Qian (Journal of Environmental Chemical Engineering, 2025)

Xuebijing Promotes HMGB1-Mediated Autophagy to Alleviate Oxidative Stress and Inflammation in Heat Stroke-Induced Brain Damage - Hongbo Li; Chunhe Li; Jun Li; Yongrui Liu; Minyong Wen; Lin Wang (Molecular Neurobiology, 2025)

Long-term simulation of saltmarsh landscape based on hydro-sediment and vegetation Dynamics: Assessing future stability - Feng Luo; Hongbo Wu; Zhipeng Chen; Jinhai Zheng; Aifeng Tao; Hongping Zhao; Yongfu Dong; Lin Lv (Estuarine, Coastal and Shelf Science, 2025)

Unraveling the role of phosphorus on V2O5-WO3-CeO2/TiO2 catalysts: Mechanisms for enhanced NH3-SCR and water resistance - Hongbo Qi; Jianwen Lai; Qiong Yuan; Yunfeng Ma; Yichao Qian; Zhongkang Han; Xiaoqing Lin; Xiaodong Li (Chemical Engineering Journal, 2025)

New polyketides and cytotoxic alkaloids from the mangrove endophytic fungus Talaromyces sp. SAF14 - Hong Li; Cankai Lin; Kaixin Chen; Zhihui Zhou; Zanhong Chen; Bo Ding; Hongbo Huang; Yiwen Tao (Natural Product Research, 2025)

Enhanced low-temperature simultaneous removal of nitrogen oxides and polychlorinated dibenzodioxins and dibenzofurans over vanadium-cerium-tungsten oxide supported on titanium dioxide catalyst: A pilot-scale evaluation - Jianwen Lai; Hongbo Qi; Yunfeng Ma; Xiaoqing Lin; Zhongkang Han; Heidelore Fiedler; Xiaodong Li (Journal of Environmental Chemical Engineering, 2025)

Cu-doped ZiF-8 and calcined UIO-66-based biomimetic enzyme electrochemical sensor for rapid and sensitive detection of Zearalenone in vegetable oil - Lin Zhiyuan; Kong Fanzhuo; Zhang Yuyang; Kouiti Oussama; Suo Hongbo; Huang Rubing; Zou Bin (Food Chemistry, 2025)

Collection, Characterization, and Diversity Analysis of New Wild Sugarcane Germplasm from Southeastern Yunnan Province, China - Chaohua Xu; Xuekuan Chen; Fenggang Zan; Peifang Zhao; Wei Qin; Chunyan Tian; Xiuqin Lin; Chunyan Kong; Hongbo Liu; Tanweer Kumar; Faisal Mehdi; Mahmoud H. M. Ebid; et al. (Sugar Tech, 2025)

Biomimetic enzyme ratiometric electrochemical sensor based on graphene, calcined UIO-66 and thionine for rapid and sensitive detection of zearalenone in vegetable oil - Lin Zhiyuan; Xie Yuzhe; Kong Fanzhuo; Xia Jiaojiao; Suo Hongbo; Huang Rubing; Zou Bin (Food Bioscience, 2025)

Intercropping improves plant biochemistry and soil microecology to realize healthy and sustainable production of Platycodon grandiflorus - Xiangui Mei; Lin Zhang; Hongbo Xu; Chuanzhi Kang; Wenshuai Sun; Lixiang Zhu; Yingying Cui; Lanping Guo (Journal of Cleaner Production, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Winter wheat harvest detection via Sentinel-2 MSI images - Jibo Yue; Yihan Yao; Jianing Shen; Ting Li; Nianxu Xu; Haikuan Feng; Yihao Wei; Xin Xu; Yinghao Lin; Wei Guo; Yuanyuan Fu; Hongbo Qiao; et al. (International Journal of Remote Sensing, 2025)

The plant retromer components SNXs bind to ATG8 and CLASP to mediate autophagosome movement along microtubules - Yanglan Liao; Xibao Li; Wenlong Ma; Xinyi Lin; Jiayi Kuang; Xuanang Zheng; Zien Li; Fanfan Qiao; Chuanliang Liu; Jun Zhou; Faqiang Li; Ruixi Li; et al. (Molecular Plant, 2025)

Association of residential greenness and sleep duration in adults: A prospective cohort study in China - Jiayi Li; Yaoyao Lin; Zongming Yang; Joachim Heinrich; Tianyu Zhao; Zhebin Yu; Wenqing Wang; Kaixuan Yang; Peng Shen; Hongbo Lin; Liming Shui; Jianbing Wang; et al. (Environmental Research, 2025)

Green remediation of REEs-contaminated soil by biodegradable chelators with optimization and risk assessment - Hongbo Li; Shiqin Long; Shoushu Wei; Qingze Chen; Xiaoju Lin; Xiaoliang Liang; Jianxi Zhu; Runliang Zhu (Environmental Pollution, 2025)

The role of miRNAs in the associations between particulate matter and ischemic stroke: A nested case-control study - Tiezheng Li; Lisha Xu; Peng Shen; Jie Qiu; Yixing Wang; Jingjing Hu; Peng Guan; Hongbo Lin; Zhiqin Jiang; Kun Chen; Jianbing Wang (Environmental Pollution, 2025)

Efficient synthesis of isoamyl acetate in deep eutectic solvent utilizing in-situ aqueous phase immobilized lipase biocatalyst - Yuyang Zhang; Qiujie Wang; Zhiyuan Lin; Jiaojiao Xia; Hongbo Suo; Rubing Huang; Bin Zou (Food Bioscience, 2025)

Vitamin C encapsulated biomimetic nanogels with macrophage membrane decoration for chronic wound healing - Xin Yang; Xiang Lin; Jinbo Li; Tapani Viitala; Yuanjin Zhao; Hongbo Zhang; Luoran Shang (Chemical Engineering Journal, 2025)

Structural Response Prediction of Floating Offshore Wind Turbines Based on Force-to-Motion Transfer Functions and State-Space Models - Jie Xu; Changjie Li; Wei Jiang; Fei Lin; Shi Liu; Hongchao Lu; Hongbo Wang (Journal of Marine Science and Engineering, 2025)
This paper proposes an innovative algorithm for forecasting the motion response of floating offshore wind turbines by employing force-to-motion transfer functions and state-space models. Traditional numerical integration techniques, such as the Newmark-β method, frequently struggle with inefficiencies due to the heavy computational demands of convolution integrals in the Cummins equation. Our new method tackles these challenges by converting the problem into a system output calculation, thereby eliminating convolutions and potentially enhancing computational efficiency. The procedure begins with the estimation of force-to-motion transfer functions derived from the hydrostatic and hydrodynamic characteristics of the wind turbine. These transfer functions are then utilized to construct state-space models, which compactly represent the system dynamics. Motion responses resulting from initial conditions and wave forces are calculated using these state-space models, leveraging their poles and residues. We validated the proposed method by comparing its calculated responses to those obtained via the Newmark-β method. Initial tests on a single-degree-of-freedom (SDOF) system demonstrated that our algorithm accurately predicts motion responses. Further validation involved a numerical model of a spar-type floating offshore wind turbine, showing high accuracy in predicting responses to both regular and irregular wave conditions, closely aligning with results from conventional methods. Additionally, we assessed the efficiency of our algorithm over various simulation durations, confirming its superior performance compared to traditional time-domain methods. This efficiency is particularly advantageous for long-duration simulations. The proposed approach provides a robust and efficient alternative for predicting motion responses in floating offshore wind turbines, combining high accuracy with improved computational performance. It represents a promising tool for enhancing the development and evaluation of offshore wind energy systems.

Fabrication of high-strength superhydrophobic aerogels via air-induced self-crosslinking for efficient oil-water separation - Fengfan Zhang; Zihao Yang; Xiaochen Li; Yaqing Hu; Kunyu Xu; Hongbo Wang; Meiqin Lin; Juan Zhang; Zhaoxia Dong (Fuel, 2025)

In-situ aqueous phase encapsulation immobilized lipase assisted by acidic ionic liquids for the synthesis of isoamyl acetate - Yuyang Zhang; Xin Gu; Zhiyuan Lin; Hongbo Suo; Jiaojiao Xia; Bin Zou (Food Bioscience, 2025)

Hierarchical gelatin-derived hydrogel film with reactive oxygen species scavenging properties for spinal cord injury repair - Haiwen Su; Yanyu Ma; Wenhan Li; Haoyu Ren; Xiayidan Maimaitikelimu; Fangsiyu Lin; Hongbo Zhang; Shuai Liu; Quanchi Chen; Huan Wang (Chemical Engineering Journal, 2025)

Investigating climatic drivers of snow phenology by considering key-substage heterogeneity - Xinqi Ma; Kai Lin; Xueyan Sun; Lun Luo; Ning Ma; Hang Zha; Longhui Zhang; Shizhen Tang; Zhiguang Tang; Hongbo Zhang (Journal of Hydrology, 2024)

Characterization of newly isolated Bacillus cereus D3 Co-producing α-amylase and protease and its application in food raw materials - Shuang Wang; Hua Bai; Zongmin Wang; Lin Peng; Ling Li; Hongbo Yan; Lanlan Zhu; Yanbo Wang; Jinyan Shao; Jizhou Liu (Food Bioscience, 2024)

Association of fine particulate matter and residential green space with rheumatoid arthritis - Jingjing Hu; Peng Shen; Yingying Mao; Jie Qiu; Lisha Xu; Yonghao Wu; Yixing Wang; Ye Ding; Hongbo Lin; Liming Shui; Tong Feng; Jianbing Wang; et al. (Environmental Research, 2024)

Outdoor light at night, air pollution and risk of incident type 2 diabetes - Yonghao Wu; Ye Jiao; Peng Shen; Jie Qiu; Yixing Wang; Lisha Xu; Jingjing Hu; Jiayun Zhang; Zihan Li; Hongbo Lin; Zhiqin Jiang; Liming Shui; et al. (Environmental Research, 2024)

Bio-inspired magnetically induced self-assembling Janus solar evaporator with antifouling and antiscaling properties - Pan Huang; Charley Huang; Yongxiang Sun; Ziqian Zhao; Lin Yang; Haoyu Yang; Lu Gong; Wenshuai Yang; Hongbo Zeng (Chemical Engineering Journal, 2024)

Photo-transformation of biochar-derived dissolved organic matter and its binding with phenanthrene/9-phenanthrol: The role of functional group and pyrolysis temperature - Yifan Niu; Siyao Wang; Peng Gao; Xin Ren; Fangfang Li; Zhanpeng Liu; Lin Wang; Hongbo Peng; Shaohua Ju (Bioresource Technology, 2024)

Investigating the cardiotoxicity of N-n-butyl haloperidol iodide: Inhibition mechanisms on hERG channels - Jilin Liao; Zhenyu Yang; Jinhua Yang; Hailing Lin; Bingxuan Chen; Hongbo Fu; Xiaojie Lin; Binger Lu; Fenfei Gao (Toxicology, 2024)

Unveiling the green path: How urban openness reduces pollution and paves the way to sustainability - Chao Zhong; Hongbo Cai; Lin Liu; Rui Xue; Yuli Shan (Journal of Environmental Management, 2024)

Corrigendum to ‘Calcium oxide adsorption of gas phase PCDD/Fs and its impact on the adsorption properties of activated carbon’ [Environ. Pollut., Volume 361, 15 November 2024, 124750 - Jianwen Lai; Peiyue Wang; Hongbo Qi; Yunfeng Ma; Zhongkang Han; Heidelore Fiedler; Xiaodong Li; Xiaoqing Lin (Environmental Pollution, 2024)

Calcium oxide adsorption of gas phase PCDD/Fs and its impact on the adsorption properties of activated carbon - Jianwen Lai; Peiyue Wang; Hongbo Qi; Yunfeng Ma; Zhongkang Han; Fiedler Heidelore; Xiaodong Li; Xiaoqing Lin (Environmental Pollution, 2024)

Generation of canine neutralizing antibodies against canine parvovirus by single B cell antibody technology - Zhihao Wang; Pengfei Shi; Sheng Wang; Zhipeng Lin; Zhichen Wang; Chengguang Zhang; Ling Zhao; Sizhu Suolang; Jiahui Zou; Hongbo Zhou (Archives of Virology, 2024)

Nanowire arrays with abundant Cu–Ni interfaces for electroreduction of CO2 to ethylene - Kunyu Xu; Haoling Yang; Yaqing Hu; Fengfan Zhang; Hongbo Wang; Yiqi Pan; Zihao Yang; Juan Zhang; Meiqin Lin; Zhaoxia Dong (Chemical Engineering Journal, 2024)

Phylogenetic analysis, genetic diversity, and epidemiology of pigeon paramyxovirus type 1 in China - Chuqi Huang; Shaoyu Tu; Wei Sheng; Zhihao Wang; Zhipeng Lin; Jing Qian; Jiahui Zou; Hongbo Zhou (Archives of Virology, 2024)

Green remediation of mercury-contaminated soil using iron sulfide nanoparticles: Immobilization performance and mechanisms, effects on soil properties, and life cycle assessment - Dongjiao Lin; Guanzhao Hu; Hongbo Li; Fan Wu; Liang Li; Guiqin Yang; Li Zhuang; Yanyan Gong (Science of The Total Environment, 2024)

Microplastic co-exposure elevates cadmium accumulation in mouse tissue after rice consumption: Mechanisms and health implications - Shan Chen; Haijun Gan; Xinying Lin; Boxuan Wang; Mengya Li; Lena Q. Ma; Dongmei Zhou; Hongbo Li (Journal of Hazardous Materials, 2024)

Engineering Au-Pt atomic alloy cocatalysts for enhanced H2 production from photo-reforming of lignocellulosic biomass wastes - Fangjie Ding; Hongbo Yu; Renyong Tu; Sha Li; Lin Chen; Bing Li; Jianzhong Guo; Chunzheng Wu (Chemical Engineering Journal, 2024)

Nanofluids with superhydrophobic nanoparticles for improved depressurization mechanism in low permeability reservoirs - Mingwei Zhao; Yuxin Xie; Lin Li; Caili Dai; Zhongzheng Xu; Yunbo Dong; Hongbo Zeng (Chemical Engineering Journal, 2024)

Genome-wide identification of 9-cis-epoxy-carotenoid dioxygenases (NCEDs) and potential function of OfNCED4 in carotenoid biosynthesis of Osmanthus fragrans - Yanxia Du; Lin Peng; Bin Dong; Shiwei Zhong; Jinping Deng; Qiu Fang; Zheng Xiao; Yiguang Wang; Hongbo Zhao (Trees, 2024)

Auto-adjustment label assignment-based convolutional neural network for oriented wheat diseases detection - Haiyun Liu; Hongbo Chen; Jianming Du; Chengjun Xie; Qiong Zhou; Rujing Wang; Lin Jiao (Computers and Electronics in Agriculture, 2024)

Enhanced lanthanum and cerium removal of self-powered electro-membrane bioreactor (SPEMBR) using high-active bi-functional M-N-CNTs@Fe/Mo electrode - Hui Lu; Hongbo Wang; Changfei Gao; Lifen Liu; Tingting Yu; Yihua Li; Shaoying Lin (Chemical Engineering Journal, 2024)

Study on Sensitivity Mechanism of Low-Permeability Sandstone Reservoir in Huilu Area of Pearl River Mouth Basin - Hongbo Li; Lin Ding; Qibiao Zang; Qiongling Wu; Yongkun Ma; Yuchen Wang; Sandong Zhou; Qiaoyun Cheng; Xin Tian; Jiancheng Niu; Mengdi Sun (Journal of Marine Science and Engineering, 2024)
Reservoir sensitivity is a parameter that is used to evaluate the degree of change in reservoir permeability under the influence of external fluids. Accurate evaluation of reservoir sensitivity is conducive to the optimization of fluid parameters during exploration and development. Taking the Wenchang Formation and Enping Formation of the Paleogene in the Huilu area of the Pearl River Mouth Basin as the research object, reservoir sensitivity experiments were carried out. Combined with the corresponding experimental results obtained using methods such as thin section identification, scanning electron microscopy (SEM), X-ray diffraction (XRD), mercury intrusion porosimetry (MIP), and screening analysis, based on mineral sensitization and pore structure sensitization, qualitative and quantitative evaluations of reservoir sensitivity were carried out, and factors affecting sensitivity and sensitization mechanisms were analyzed. This work shows the following: (1) The sandstone reservoirs in the two areas have the same clay type, but the total clay content of the Wenchang Formation is greater than that of the Enping Formation. The porosity of the Wenchang Formation is less developed than the Enping Formation. (2) The Wenchang Formation has weak or moderately weak water sensitivity and moderately weak or moderately strong flow velocity sensitivity. The water sensitivity of the Enping Group samples is moderately weak or moderately strong, the flow rate sensitivity is moderately weak, the alkali sensitivity is weak, the acid sensitivity is moderately weak, and the salinity sensitivity is moderately weak or moderately strong. (3) The sensitivity of the Wenchang Formation is mainly affected by the content of clay minerals. The sensitivity of the Enping Formation is also affected by the clay content and type. Although the clay content is not high, the permeability is more susceptible to sensitivity due to the pore structure and debris particle distribution characteristics. These conclusions are beneficial for the selection of fluid parameters and efficient reservoir development.

Urchin-like CO2-responsive magnetic microspheres for highly efficient organic dye removal - Lin Yang; Yongxiang Sun; Ruiquan Yu; Pan Huang; Qi Zhou; Haoyu Yang; Shaojian Lin; Hongbo Zeng (Journal of Hazardous Materials, 2024)

Design of Pt@Sn core–shell nanocatalysts for highly selective hydrogenation of cinnamaldehyde to prepare cinnamyl alcohol - Shuibo Wang; Biao Wu; Qiuju Zhang; Yiming Li; Lin Zhu; Hongbo Yu; Hongfeng Yin (Chemical Engineering Journal, 2024)

Enhanced removal of 2,4-dichlorophenol by coupling of Pd nanoparticles with biofilm - Chengyang Wu; Jingzhou Zhou; Si Pang; Lin Yang; Xiaodi Li; Eric Lichtfouse; Siqing Xia; Hongbo Liu (Journal of Environmental Chemical Engineering, 2024)

Degradation of triclosan by peroxydisulfate/peroxomonosulfate binary oxidants activation under thermal conditions: Efficiency and mechanism - Zhimin Xu; Zhanpeng Liu; Shunling Li; Fangfang Li; Peng Gao; Siyao Wang; Youcheng Lin; Guomei Xiong; Zhiqun Li; Hongbo Peng (Journal of Environmental Management, 2024)

Reduction and precipitation of chromium(VI) using a palladized membrane biofilm reactor - Chengyang Wu; Jingzhou Zhou; Si Pang; Lin Yang; Eric Lichtfouse; Hongbo Liu; Siqing Xia; Bruce E. Rittmann (Water Research, 2024)

A study of land use changes and its impacts on flood inundation in the Konkoure River Basin, Republic of Guinea - Alhassane Bah; Hongbo Zhang; Zhumei Luo; Jimin Hu; Zulian Zhang; Yang Lin Xie; Ting Yang; Guohong Chen; Alseny Bah (Environmental Monitoring and Assessment, 2024)

Foliar spraying of lanthanum activates endocytosis in lettuce (Lactuca sativa L.) root cells, increasing Cd and Pb accumulation and their bioaccessibility - Xinyan Zong; Yongqiang Liu; Xinying Lin; Ding He; Zhongtian Dong; Ting Guo; Jining Li; Hongbo Li; Fenghe Wang (Science of The Total Environment, 2024)

Towards in-depth profile control using dispersed particle gels (DPGs) - Lin Du; Yao-Yu Xiao; Zhi-Chao Jiang; Hongbo Zeng; Huazhou Li (Fuel, 2023)

Antibacterial food packaging capable of sustained and unidirectional release carvacrol/thymol nanoemulsions for pork preservation - Lin Wang; Mengyuan Yuan; Enze Sun; Jiang Wu; Anboyuan Lv; Xu Zhang; Jiaxiang Guo; Yu Zhu; Hongbo Guo; Xiaozhou Li; Ke Wang (Food Hydrocolloids, 2023)

Genome architecture and tetrasomic inheritance of autotetraploid potato - Zhigui Bao; Canhui Li; Guangcun Li; Pei Wang; Zhen Peng; Lin Cheng; Hongbo Li; Zhiyang Zhang; Yuying Li; Wu Huang; Mingwang Ye; Daofeng Dong; et al. (Molecular Plant, 2023)

Ultralong hydroxyapatite nanowires-based flow-through reactor with high loading of silver nanoparticles for fast continuous catalytic reduction of organic dyes and disinfection of wastewater - Pan Huang; Wanyi Fang; Lin Yang; Yongxiang Sun; Haoyu Yang; Xing-Zhen Chen; Hongbo Zeng (Chemical Engineering Journal, 2023)

Self-similarity convolution neural network for seismic noise suppression in desert environment - Hongbo Lin; Xinyu Xu; Shigang Wang (Studia Geophysica et Geodaetica, 2023)

Formation mechanisms of nano-aluminum oxide-dissolved black carbon and their adsorption for norfloxacin and phenanthrene - Hongbo Peng; Junjian Lin; Dong Yang; Peng Gao; Siyao Wang; Jie Yang; Zhimin Xu; Fangfang Li (Journal of Soils and Sediments, 2023)

Semen damage contributed over 50 % to air-pollutant-induced infertility: A prospective cohort study of 3940 men in China - Ying Guo; Qing Chen; Yu Zhan; Wenzheng Zhou; Haiyan Zhang; Niya Zhou; Huan Yang; Yi Chen; Yimeng Wang; Lei Sun; Lin Ao; Jinyi Liu; et al. (Science of The Total Environment, 2023)

Asymmetric learning based deep denoiser for nonstationary desert seismic noise suppression - Hongbo Lin; Xue Song; Shifu Wang; Haitao Ma; Xuejun Wang (Computers & Geosciences, 2023)

Physiological response of red macroalgae Pyropia yezoensis (Bangiales, Rhodophyta) to light quality: a short-term adaptation - Xuefeng Zhong; Shuai Che; Congying Xie; Lan Wu; Xinyu Zhang; Lin Tian; Chan Liu; Hongbo Li; Guoying Du (Algae, 2023)
Light quality is a common environmental factor which influences the metabolism of biochemical substances in algae and leads to the response of algal growth and development. Pyropia yezoensis is a kind of economic macroalgae that naturally grows in the intertidal zone where the light environment changes dramatically. In the present study, P. yezoensis thalli were treated under white light (control) and monochromatic lights with primary colors (blue, green, and red) for 14 days to explore their physiological response to light quality. During the first 3 days of treatment, P. yezoensis grew faster under blue light than other light qualities. In the next 11 days, it showed better adaptation to green light, with higher growth rate and photosynthetic capacity (reflected by a higher rETRmax = 61.58 and Ek = 237.78). A higher non-photochemical quenching was observed in the treatment of red light than others for 14 days. Furthermore, the response of P. yezoensis to light quality also results in the difference of photosynthetic pigment contents. The monochromatic light could reduce the synthesis of all pigments, but the reduction degree was different, which may relate to the spectral absorption characteristics of pigments. It was speculated that P. yezoensis adapted to a specific or changing light environments by regulating the synthesis of pigments to achieve the best use of light energy in photosynthesis and premium growth and metabolism.

Residential greenness, air pollution and incident neurodegenerative disease: A cohort study in China - Zhanghang Zhu; Zongming Yang; Luhua Yu; Lisha Xu; Yonghao Wu; Xinhan Zhang; Peng Shen; Hongbo Lin; Liming Shui; Mengling Tang; Mingjuan Jin; Jianbing Wang; et al. (Science of The Total Environment, 2023)

Sex-specific effect of perfluoroalkyl substances exposure on liver and thyroid function biomarkers: A mixture approach - Ze Yang; Ruifang Liu; Hongbo Liu; Jiemin Wei; Xiaohui Lin; Mingyue Zhang; Yu Chen; Jingyun Zhang; Meiqing Sun; Zhe Feng; Jian Liu; Xiangyang Liu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Responsive Transcriptome Analysis of Senecio vulgaris L. Under Different Drought Stresses - Hongbo Pang; Yuanming Wu; Yueying Li; Longkun Wu; Ze Wang; Lin Chang; Hongxin Liu; Qiang Chen (Journal of Plant Growth Regulation, 2023)

High-Intensity Ultraviolet-C Irradiation Efficiently Inactivates SARS-CoV-2 Under Typical Cold Chain Temperature - Peiru Li; Xianliang Ke; Dongmei Leng; Xian Lin; Wenling Yang; Hainan Zhang; Changqing Tian; Hongbo Xu; Quanjiao Chen (Food and Environmental Virology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

FexO4-enhanced degradation of bisphenol A in visible light/peroxydisulfate system: production of singlet state oxygen - Zhimin Xu; Shaohua Ju; Peng Gao; Junjian Lin; Yifan Niu; Fei Meng; Shunling Li; Fangfang Li; Jiahao Du; Li Xu; Hongbo Peng; Bo Pan (Environmental Science and Pollution Research, 2023)

Attention mechanism-based deep denoiser for desert seismic random noise suppression - Hongbo Lin; Chang Liu; Shigang Wang; Wenhai Ye (Acta Geophysica, 2023)

Evaluation of drought tolerance in sugarcane genotypes using the membership function value of drought tolerance (MFVD) - Chaohua Xu; Jun Mao; Xujuan Li; David M. Burner; Chunjia Li; Shareif H. Hussin Hussin; Xiuqin Lin; Hongbo Liu; Peifang Zhao; Xin Lu; Xinlong Liu (Euphytica, 2023)

Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Yonghao Wu; Peng Shen; Zongming Yang; Luhua Yu; Zhanghang Zhu; Tiezheng Li; Lisha Xu; Dan Luo; Xuecheng Yao; Xinhan Zhang; Lin Meng; Hongbo Lin; et al. (Science of The Total Environment, 2023)

Association between exposure to perfluoroalkyl substances and uric acid in Chinese adults - Ze Yang; Kun Men; Jiaxin Guo; Ruifang Liu; Hongbo Liu; Jiemin Wei; Jingyun Zhang; Liangpo Liu; Xiaohui Lin; Mingyue Zhang; Yong Liu; Yu Chen; et al. (Chemosphere, 2023)

Effective multipurpose sewage sludge and food waste reduction strategies: A focus on recent advances and future perspectives - Xuefeng Zhu; Yuting Xu; Guangyin Zhen; Xueqin Lu; Suyun Xu; Jie Zhang; Lin Gu; Haifeng Wen; Hongbo Liu; Xuedong Zhang; Zhichao Wu (Chemosphere, 2023)

Research on the on-line fracture assessment of cracked primary loop pipes in NPPs - Mingya Chen; Hongbo Gao; Lei Lin; Decheng Xu; Shuai Zhou; Weiqiang Wang; Jinhua Shi; Qunjia Peng; Zhilin Chen (Annals of Nuclear Energy, 2023)

Impact of salinity origin on microbial communities in saline springs within the Illinois Basin, USA - Linduo Zhao; Hongbo Shao; Li Zhang; Samuel V. Panno; Walton R. Kelly; Tzu‐Yu Lin; Wen‐Tso Liu; Theodore M. Flynn; Peter Berger (Environmental Microbiology, 2022)
Saline springs within the Illinois Basin result from the discharge of deep‐seated evaporated seawater (brine) and likely contain diverse and complex microbial communities that are poorly understood. In this study, seven saline/mineral springs with different geochemical characteristics and salinity origins were investigated using geochemical and molecular microbiological analyses to reveal the composition of microbial communities inhabiting springs and their key controlling factors. The 16S rRNA sequencing results demonstrated that each spring harbours a unique microbial community influenced by its geochemical properties and subsurface conditions. The microbial communities in springs that originated from Cambrian/Ordovician strata, which are deep confined units that have limited recharge from overlying formations, share a greater similarity in community composition and have a higher species richness and more overlapped taxa than those that originated from shallower Pennsylvanian strata, which are subject to extensive regional surface and groundwater recharge. The microbial distribution along the spring flow paths at the surface indicates that 59.8%–94.2% of total sequences in sedimentary samples originated from spring water, highlighting the role of springs in influencing microbiota in the immediate terrestrial environment. The results indicate that the springs introduce microbiota with a high biodiversity into surface terrestrial or aquatic ecosystems, potentially affecting microbial reservoirs in downstream ecosystems.

Experimental and Numerical Study of the Discharge Performance of Particle-Laden Turbulent Flow - Hongbo Shi; Xikun Wang; Qingjiang Xiang; Gonghe Zhang; Lin Xue (Journal of Marine Science and Engineering, 2022)
In the marine fire suppression system, continuous delivery of dry chemical powder to the fire source with long powder discharge range and high dispersion concentration is essential. The work is devoted to experimental and numerical studies of the flow characteristics of the dry chemical powder jet from a horizontal injector with a wide range of Stokes numbers between 6 to 30 and Reynolds numbers between 4792 to 23,960 by considering the effect of gravitational acceleration. A CFD-based Eulerian–Eulerian multiphase model combined with Standard k-ω turbulence model was used to predict flow characteristics of particle-laden jet using dimensionless numbers, including the solid volume fraction, the normalized velocity magnitude, and the turbulent viscosity ratio. Experimental studies have been carried out for three different inflow velocities (2.06, 2.45, and 2.81 m/s). The results indicate that the particle density plays a significant role in the dispersion of the particles in the radial and axial directions. The transition from U-shaped to V-shaped solid dispersion structure on the ground can be captured with the increase of particle density. Moreover, the higher level turbulence intensity enhances the solid dispersion concentration. Finally, it was found that the Portland cement powder exhibits better discharge performance in terms of solid discharge range and dispersion concentration in comparison with other dry powders. These results have implications in the design of powder-based fire suppression system. Further studies should aim to the in-depth research on the fire extinguishing mechanism of the Portland cement powder, especially the fire suppression effectiveness and thermal decomposition process.

3D finite-element modeling of Earth induced electromagnetic field and its potential applications for geomagnetic satellites - Hongbo Yao; Zhengyong Ren; Jingtian Tang; Yufeng Lin; Changchun Yin; Xiangyun Hu; Qinghua Huang; Keke Zhang (Science China Earth Sciences, 2021)

Detection of Key Brown Rust Resistance Gene, Bru1, in 200 Sugarcane (Saccharum L.) Ancestral Species and Landraces Using a Four-Primer Molecular Marker - Xujuan Li; Chaohua Xu; Jun Mao; Hongbo Liu; Chunjia Li; Xinlong Liu; Xiuqin Lin; Chunyan Kong; Xin Lu (Sugar Tech, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

Transcriptome analysis of axillary bud differentiation in a new dual-axillary bud genotype of sugarcane - Dan Chen; Xin Lu; Xiaoyang Wu; Xiongmei Ying; Wenjie Long; Huosheng Su; Hongbo Liu; Xiuqin Lin; Chaohua Xu; Qing Cai (Genetic Resources and Crop Evolution, 2020)

Characterization of a novel echovirus 21 strain isolated from a healthy child in China in 2013 - Hongbo Liu; Shanri Cong; Danhan Xu; Keqin Lin; Xiaoqin Huang; Hao Sun; Zhaoqing Yang; Shaohui Ma (Archives of Virology, 2020)

Roles of Synoptic to Quasi-Monthly Disturbances in Generating Two Pre-Summer Heavy Rainfall Episodes over South China - Zhina Jiang; Da-Lin Zhang; Hongbo Liu (Advances in Atmospheric Sciences, 2020)

Association of particulate matter air pollution and hospital visits for respiratory diseases: a time-series study from China - Zhenyu Zhang; Pengfei Chai; Jianbing Wang; Zhenhua Ye; Peng Shen; Huaichu Lu; Mingjuan Jin; Mengjia Gu; Die Li; Hongbo Lin; Kun Chen (Environmental Science and Pollution Research, 2019)

Trace metal pollution and ecological risk assessment in agricultural soil in Dexing Pb/Zn mining area, China - Junjie Hu; Boji Lin; Meiyi Yuan; Zhilang Lao; Kangming Wu; Yanyan Zeng; Zhihui Liang; Huiru Li; Yanliang Li; Dan Zhu; Junlong Liu; Hongbo Fan (Environmental Geochemistry and Health, 2019)

Desert seismic random noise reduction based on LDA effective signal detection - Haitao Ma; Jie Yan; Yue Li; Chao Zhang; Hongbo Lin (Acta Geophysica, 2019)

Noise reduction for desert seismic data using spectral kurtosis adaptive bandpass filter - Haitao Ma; Zebin Qian; Yue Li; Hongbo Lin; Dan Shao; Baojun Yang (Acta Geophysica, 2019)

Diversity of the cyrtophorid genus Chlamydodon (Protista, Ciliophora): its systematics and geographic distribution, with taxonomic descriptions of three species - Zhishuai Qu; Lifang Li; Xiaofeng Lin; Thorsten Stoeck; Hongbo Pan; Khaled A. S. Al-Rasheid; Weibo Song (Systematics and Biodiversity, 2018)

First arrival time picking for microseismic data based on DWSW algorithm - Yue Li; Yue Wang; Hongbo Lin; Tie Zhong (Journal of Seismology, 2018)

Di-(2-ethylhexyl)-phthalate induces glucose metabolic disorder in adolescent rats - Jin Xu; Liting Zhou; Shuyue Wang; Jian Zhu; Te Liu; Yiyang Jia; Di Sun; Huaiji Chen; Qi Wang; Feng Xu; Yuezhu Zhang; Hongbo Liu; et al. (Environmental Science and Pollution Research, 2018)

An Assessment of Genetic Diversity of Yield-Related Traits of Saccharum spontaneum from Yunnan Province, China - Chaohua Xu; Huosheng Su; Hongbo Liu; Xin Lu; Xujuan Li; Chunjia Li; Xiuqin Lin; Jun Mao; Qiuyan Zi; XinLong Liu (Sugar Tech, 2017)

Peroxisome proliferator-activated receptor alpha mediates C/EBP homologous protein to protect mice from acute liver failure - Xiangying Zhang; Peiling Dong; Hongbo Shi; Huaying Sun; Jianhui Lin; Dexi Chen; Zhongping Duan; Xiuhui Li; Feng Ren (Inflammation Research, 2017)

Removal of Random Noise in Seismic Data by Time-varying Window-length Time-frequency Peak Filtering - Pengjun Yu; Yue Li; Hongbo Lin; Ning Wu (Acta Geophysica, 2016)

Applications of Savitzky-Golay Filter for Seismic Random Noise Reduction - Yanping Liu; Bo Dang; Yue Li; Hongbo Lin; Haitao Ma (Acta Geophysica, 2016)

Influence of Val108/158Met COMT Gene Polymorphism on the Efficacy of Modified Electroconvulsive Therapy in Patients with Treatment Resistant Depression - Zhaoyu Lin; Hongbo He; Chunping Zhang; Zhijie Wang; Miaoling Jiang; Qirong Li; Xiaochang Lan; Minling Zhang; Xiong Huang (Cell Biochemistry and Biophysics, 2015)

Pharmaceutical residues in tidal surface sediments of three rivers in southeastern China at detectable and measurable levels - Yongshan S. Chen; Shen Yu; Youwei W. Hong; Qiaoying Y. Lin; Hongbo B. Li (Environmental Science and Pollution Research, 2013)

Suppression of strong random noise in seismic data by using time-frequency peak filtering - Yue Li; BaoJun Yang; HongBo Lin; HaiTao Ma; PengFei Nie (Science China Earth Sciences, 2013)

Cholecystectomy and risk of pancreatic cancer: a meta-analysis of observational studies - Genlai Lin; Zhaochong Zeng; Xiaolin Wang; Zheng Wu; Jian Wang; Chenggang Wang; Qiao Sun; Yixing Chen; Hongbo Quan (Cancer Causes & Control, 2012)